Diseño y construcción de un sistema electromecánico autónomo para vencer la inercia de arranque de los aerogeneradores de eje vertical del AEIRNNR. - Moreno Ponce, Juan Manuel (2013)
The present qualified work of thesis " Design and construction of an electromechanical autonomous system to conquer the inertia of take-off of the wind generators of vertical axis of the AEIRNNR ", has the purpose the contribute efficiently and directly to the take-off of the wind generators for the later utilization of the wind resource and as it is an autonomous system, for his supply also he will take advantage of the solar resource across photovoltaic panels. Consist of a system of new start and of a current technology composed by two starters, due to the fact that your transmission by means of toothed wheel and pinion resulted acceptable and precise for the requirements of the system, being more important the time of take-off to conquer the inertia in the mobile components of wind turbines. In a concise way it is possible to mention that the raised system consists of an anemometer which sends the sign of functioning to start the engines of take-off under certain conditions of the wind resource. A mini PLC entrusts himself of receptar the sign of the anemometer and sending signs to the operations to command the circuit of force and of control when this one like that needs it. Finally, the system assures his autonomy by means of the implementation of a system of obtaining and accumulation of electric power by means of solar power. All these elements form the self-sufficient system of obtaining, accumulation, transformation and sure supply of direct current, capable of settling the energetic requirement of the system of take-off for the wind generators. The dimensionamiento was based on meteorological studies previously realized in the site of emplacement of the wind generators the same ones they allowed to conclude on the escaza feasibility on the part of the wind generators for wind utilization due to his high couple of inertia, but in turn they gave to us the idea of implementation of our system of take-off.